Settlers, Suffrage, and Transnational Women’s History in Imperial Plots - Campbell, Lara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
Sarah Carter’s Imperial Plots: Women, Land, and the Spadework of Colonialism on the Canadian Prairies sits at the intersection of women’s history, histories of settler colonialism, and the history of the West. This reflection asks whether (and to what extent) national borders shape the way historians do transnational women’s history and highlights how Western settler colonialism and ideas about gender, race, and political citizenship shaped access to land.